Collectivity in A approximately equal to 60 nuclei: Superdeformed and smoothly terminating rotational bands - Svensson, Carl E. (My University, 1998)
The proton-rich nuclei in the A ? 60 mass region provide an excellent laboratory for studying the interplay between single-particle and collective nuclear excitations. In order to increase the sensitivity of spectroscopic studies of these nuclei, a new method of channel selection based on the measurement of the total energy of all ? rays and charged particles emitted in fusion-evaporation reactions has been developed. This method has been used to identify and study deformed and superdeformed (SD) rotational bands in 62 Zn and the N = Z nucleus 60 Zn. Two sets of strongly coupled rotational bands have been identified in 62 Zn and have been observed up to the terminating states of their respective configurations. Lifetime measurements indicate that the transition quadrupole moments in these bands decrease as termination is approached. These results represent the first observation of the terminating states of rotational bands in the A ? 60 mass region and confirm the predicted loss of collectivity associated with the phenomenon of smooth band termination. The first superdeformed rotational band in the A ? 60 mass region has also been identified in 62 Zn, establishing a new region of superdeformation for nuclei with neutron and proton numbers N , Z [approximate] 30. The doubly-magic superdeformed band in the N = Z nucleus 60 Zn has been identified. This band corresponds to filling the single-particle orbitals up to the large SD shell gaps at N , Z = 30 and is the natural reference core for the study of A ? 60 superdeformation. In addition, the observation of linking transitions connecting this band to normal deformed (ND) states provides the first spin, parity, and excitation energy measurements for A ? 60 SD states. The stretched- E 2 character and relatively large B (E 2) values of these linking transitions indicate that the decay-out mechanism in 60 Zn differs significantly from that observed in heavier nuclei.
Keywords: Physics; Physics